Brain Activity Changes in Slow 5 and Slow 4 Frequencies in Patients With Optic Neuritis: A Resting State Functional MRI Study - Yan, Kai; Shi, Wen-Qing; Su, Ting; Liao, Xu-Lin; Wu, Shi-Nan; Li, Qiu-Yu; Yu, Jing; Shu, Hui-Ye; Zhang, Li-Juan; Pan, Yi-Cong; Shao, Yi (Frontiers in Neurology, 2022)
Objective: We used the amplitude of low-frequency fluctuation (ALFF) method to investigate spontaneous brain activity in patients with optic neuritis (ON) in specific frequency bands. Data and methods: A sample of 21 patients with ON (13 female and 8 male) and 21 healthy controls (HCs) underwent functional magnetic resonance imaging (fMRI) scans in the resting state. We analyzed the ALFF values at different frequencies (slow-4 band: 0.027–0.073 Hz; slow-5 band: 0.01–0.027 Hz) in ON patients and HCs. Results: In the slow-4 frequency range, compared with HCs, ON patients had apparently lower ALFF in the c discuss insula and the whack precuneus. In the slow-5 frequency range, ON patients showed significantly increased ALFF in the left parietal inferior and the left postcentral. Conclusion: Our results suggest that ON may be involved in abnormal brain function and can provide a basis for clinical research.